Becoming Bilingual: A View Towards Communicative Competence - Lilla Musyahda (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
The phenomenon of foreign language mastery shall always be the main issue in the pedagogy since it has numerous advantages in human life, especially in terms of economic value. The definition of bilingualism is connected with the speaking of two languages or expression in two languages and it can be used to describe societies or individuals (Lyon, 1995). The way that a bilingual adapts to a certain condition leads to a certain phenomenon, which is quite interesting to analyze. The texture of the bilinguals creativity is essentially the result of the process of translation and transcreation, and insightful approaches to stylistics-its theory and methodology must be take into consideration. When people speak more than one languages, they may have different levels of proficiency in each of the languages, and use them for very different social purposes and in different situations. The languages that a bilingual speaks affect each other in various ways, so much that there is a regular study of what happens when one language comes into contact with another. In educational setting, it is important to know how a bilinguals first language may affect the function of other languages. The paper will discuss the phenomenon of bilingual and the implication towards communicative competence which would consists, minimally, of four areas of knowledge and skills; grammatical competence, sociolinguistic competence, discourse competence and strategic competence.